A constellation of vital phenomena : a novel - Marra, Anthony (Hogarth, 2013)
In a rural village in December 2004 Chechnya, a failed doctor Akhmed harbors the traumatized 8-year-old daughter of a father abducted by Russian forces and treats a series of wounded rebels and refugees while exploring the shared past that binds him to the child.